Genipin-crosslinked polyvinyl alcohol/silk fibroin/nano-hydroxyapatite hydrogel for fabrication of artificial cornea scaffolds—a novel approach to corneal tissue engineering. Issue 17 (22nd November 2019) - Zhou, Haohao; Wang, Zegong; Cao, Huiqun; Hu, Huiyuan; Luo, Zhongkuan; Yang, Xinlin; Cui, Mengmeng; Zhou, Li
Abstract: Design of artificial corneal scaffolds substitute is crucial for replacement of impaired cornea. In this paper, porous polyvinyl alcohol/silk fibroin/nano-hydroxyapatite (PVA/SF/n-HA) composite hydrogel was prepared via the genipin (GP) cross-linking, the pore diameter of the hydrogel ranged from 8.138 nm and 90.269 nm, and the physical and physiological function of hydrogel were investigated. The resulting hydrogel exhibited favourable physical properties. With the GP content increasing, the structural regularity of PVA/SF/n-HA composite hydrogel was enhanced and the thermal stability was improved. The moisture content was slightly decreased and generally maintained at approximately 70%. The tensile strength was heightened up to 0.64 MPa, while the breaking elongation was decreased slightly. Moreover, the biofunction was investigated. The in vitro degradation test demonstrated that with the addition of GP, the stability of the composite hydrogels in protease XIV solution was promoted and the three-dimensional porosity structure of composite hydrogels was maintained as ever. And the human corneal fibroblasts (HCFs) were employed to examine the cells cytotoxicity of the PVA/SF/n-HA composite hydrogels with different GP content by CCK-8 assay. Based on confocal laser scanning microscope (CLSM) and scanning electron microscope (SEM), HCFs had individually commendable adhesion and proliferation on PVA/n-HA/SF composite hydrogel. HCFs proliferated and grew into the pores of composite hydrogel. The results of biocompatibility experiments of composite hydrogel suggested that it was no acute toxicity, in vitro cytotoxicity was 0 or 1 grade. Overall, results from this paper, PVA/n-HA/SF composite hydrogel was a qualified medical material which conformed to the national standard, could be a promising alternative for artificial cornea scaffold material—a novel approach to corneal tissue engineering.